Synthesis and study of carbon microspheres for use as catalyst support for cobalt - Mhlanga, S.D.; Mondal, K.C.; Naidoo, N.; Witcomb, M.J.; Coville, N.J. (South African Journal of Science, 2010)
The production of pure carbon spheres was achieved in the absence of a catalyst through the direct pyrolysis of two hydrocarbon sources, acetylene and ethylene. Systematic studies using acetylene as the feedstock indicated that the size distribution of the resulting carbon microspheres can be controlled by pyrolysis temperature, time and feedstock flow rate. The resulting spheres were fully characterised by transmission electron microscopy (TEM) and thermogravimetric analysis. The TEM examination showed that these spheres have a ball-like and chain-like morphology, and the balls have smooth surfaces with a variation in diameter size and distribution determined by the reaction conditions. Carbon microsphere-supported cobalt catalysts were synthesised and have shown good activity in the ethylene hydrogenation reaction.